(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Acne vulgaris is a common inflammatory skin diseases seen in all age types, caused by the bacteria Propionibacterium acnes. Syzygium (S.) aromaticum (clove) is an aromatic plant with rich volatile compounds and antioxidants showing high antimicrobial properties mainly anti-acne property. In recent years, computational databases and methods have been shown to be an invaluable resource for research in the field of dermatology and skin health. The structural diversity of plant-derived phytochemicals with antiacne properties against receptor bacterial proteins involved in acne signaling pathways is facilitated by molecular docking studies. The present study reports the protein-ligand interaction of P. acnes bacterial protein and several phytochemicals present in S. aromaticum which acts as ligands. Thus the authors have made an effort to evaluate the anti-acne properties various phytochemicals against the predominant proteins of bacteria, P. acnes. Among the selected phytochemicals, Dillapiol showed the highest binding affinity with most number of Hydrogen bonds.